Evolution of multidimensional energy poverty risk in Bolivia from 2005 to 2019 - Javier Aliaga Lordemann; Sergio Mansilla (Institute for Advanced Development Studies (INESAD), 2023)
"Energy poverty" is a multidimensional concept that reflects the need to achieve a variety of wellbeing outcomes, which has been scarcely studied and used in public policy agendas. Considering that the literature on energy poverty is still incipient in Bolivia, this paper's objective is to generate evidence about energy poverty evolution in the country, approximating measures of incidence (risk) and severity for the period 2005-2019. The methodological approach follows the one proposed by Alkire & Foster (2011), with five equally weighted dimensions (energy expenditure, lighting, cooking fuel and indoor pollution, food equipment, and education and communication) and using different cut-off options, at the urban and rural levels. Also, Multidimensional Energy Poverty results are compared with a Principal Component Analysis (PCA) based weight structure as a robustness exercise. Results show that the risk of being energy poor in Bolivia has decreased, but not structurally. Also, intensity has decreased in both urban and rural areas, but rural energy poor households continue to show at least 50% of deprivation in all dimensions evaluated.
Keywords: I32; O13; Q40; 330; Multidimensional Poverty; Energy; Development